Functionalized GelMA/CMCS Composite Hydrogel Incorporating Magnesium Phosphate Cement for Bone Regeneration - Xingyu Wang; Xiping Zhang; Changtian Gong; Jian Yang; Jingteng Chen; Weichun Guo (Biomedicines)
Background: Bone regeneration remains a challenging issue in tissue engineering. The use of hydrogels as scaffolds for bone tissue repair has gained attention due to their biocompatibility and ability to mimic the extracellular matrix. This study aims to develop a functionalized GelMA/CMCS composite hydrogel incorporating magnesium phosphate cement (MPC) for enhanced bone regeneration. Methods: These composites were developed by incorporating potassium magnesium phosphate hexahydrate (KMgPO4·6H2O, MPC) powders into methacrylated gelatin/carboxymethyl chitosan (GelMA-C) hydrogels. The material’s mechanical properties, antibacterial performance, and cytocompatibility were evaluated. In vitro experiments involved cell viability and osteogenic differentiation assays using rBMSCs as well as angiogenic potential assays using HUVECs. The hydrogel was also assessed for its potential in promoting bone repair in a rat (Sprague-Dawley) model of bone defect. Results: The developed GelMA-CM composite demonstrated improved mechanical properties, biocompatibility, and osteogenic potential compared to individual GelMA or CMCS hydrogels. Incorporation of MPC facilitated the sustained release of ions which promoted osteogenic differentiation of pre-osteoblasts. In vivo results indicated accelerated bone healing in the rat bone defect model. Conclusions: The functionalized GelMA-CM composite could be a viable candidate for clinical applications in bone regeneration therapies.